(untitled) (Czech Journal of International Relations, 1966)
The 20th century is characterized by an accelerated pace of scientific, technical and social development, so it sometimes gives the impression that history is catching up with what was previously missed and neglected. Never in the past has humanity experienced so many far-reaching changes in the field of politics, so many revolutionary discoveries in the field of science and technology in the course of a single generation, as in the course of the last few decades. The turbulent development of the liberation movement and the emergence of a number of new states on the ruins of former colonial empires is - after the Great October Revolution - one of the most significant manifestations of this accelerated historical process.